Enhancing health‐care workers' understanding and thinking about people living with co‐occurring mental health and substance use issues through consumer‐led training. (10th October 2013) - Roussy, Véronique; Thomacos, Nikos; Rudd, Annette; Crockett, Belinda
Abstract: Background: Stigma and judgemental assumptions by health workers have been identified as key barriers to accessing health care for people living with co‐occurring mental health and substance use issues (dual diagnosis). Objective: To evaluate the effectiveness of consumer‐led training by people with dual diagnosis in improving the knowledge, understanding and role adequacy of community health staff to work with this consumer group. Methods: A controlled before‐and‐after study design with four waves of quantitative data collection was used. Qualitative data were collected to explore participants' views about training. Participants were staff from two community health services from Victoria, Australia. Recruitment occurred across various work areas: reception, oral health, allied health, counselling and health promotion. At baseline, all participants attended a 4‐h clinician‐led training session. The intervention consisted of a 3‐h consumer‐led training session, developed and delivered by seven individuals living with dual diagnosis. Outcome measures included understanding of dual diagnosis, participants' feelings of role adequacy and role legitimacy, personal views, and training outcomes and relevance. Results: Consumer‐led training was associated with a significant increase in understanding. The combination of clinician‐led and consumer‐led training was associated with a positive change in role adequacy. Conclusions: Consumer‐led training is a promising approach to enhance primary health‐care workers' understanding of the issues faced by dual‐diagnosis consumers, with such positive effects persisting over time. Used alongside other organizational capacity building strategies, consumer‐led training has the potential to help address stigma and judgemental attitudes by health workers and improve access to services for this consumer group.